2017
DOI: 10.2147/rmhp.s136844
|View full text |Cite
|
Sign up to set email alerts
|

Fractures in Kuwait: incidence and distribution

Abstract: The absence of descriptive epidemiological data on the frequency and distribution of fractures in a population is serious and may underestimate the actual importance of this public health problem. In this study, we report the crude and standardized incidence rates of fractures in the population of Kuwait during the period 2009–2012. Using the Ministry of Public Health’s national registry, demographic data of all fracture cases between 2009 and 2012 were retrieved. These were further categorized into fractures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Moreover, point biserial correlation and Ferguson's sigma values which are an item-total correlation and discriminatory power, respectively, were within the acceptable range and indicated that the tool is reliable and discriminating [23,32]. *Sum of the potential range for the Exercise subscale and Calcium intake subscale was larger than total potential range because the two subscales shared nine common questions (1)(2)(3)(4)(5)(6)(7)(8)(9). The results showed low correct answer frequencies for all dimension with low overall knowledge score.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, point biserial correlation and Ferguson's sigma values which are an item-total correlation and discriminatory power, respectively, were within the acceptable range and indicated that the tool is reliable and discriminating [23,32]. *Sum of the potential range for the Exercise subscale and Calcium intake subscale was larger than total potential range because the two subscales shared nine common questions (1)(2)(3)(4)(5)(6)(7)(8)(9). The results showed low correct answer frequencies for all dimension with low overall knowledge score.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Azizieh. (14) From Kuwait, an increase of 3.9% in annual incidence rates for all fractures was seen over 2009-2012. Shukla and Khandekar.…”
Section: Discussionmentioning
confidence: 99%
“…Studies report variable rates of incidence for hip fracture in these countries for example, a study from Kuwait reported an age-standardized rate of 48.4 per 100,000 population/year. (14) On the other hand, a study from Morocco stated that age-standardized rate of hip fracture is 69 per 100,000 population/year. (15) The outcomes of fracture are also important.…”
mentioning
confidence: 99%